INJURY PREVENTION AND MOBILITY ENHANCEMENT FOR THE COMMUNITY IN OPEN PUBLIC SPACES IN JAKARTA - Chairunisa, Ratu; Dewi, Astrid Komala; Hermawan Salim, Catherine; Wahdini, Rizqa; Sibualamu, Khalida Ziah; Nur, Galuh Dwi Pramesti; Saputra, Arianto Dwi; Fachri, Salfa Fauzziah (LPPM Univ. Ibn Khaldun Bogor, 2025)
Musculoskeletal disorders and mobility limitations are prevalent health concerns in urban communities. Inadequate understanding of safe movement patterns and the absence of structured physical activity often increase the risk of injury and reduce quality of life. To address this issue, a Community Service Program (PKM) titled “Injury Prevention and Mobility Enhancement for the Community in Open Public Spaces in Jakarta” was conducted at the Car Free Day (CFD) area of Monas. The program involved 119 participants, with 50 completing both pre- and post-test evaluations. The primary goal was to enhance movement literacy and raise awareness of safe mobility practices. Activities were organized into preparation, implementation, and evaluation stages. Interactive education was delivered through counseling and demonstrations of dynamic warm-ups, balance exercises, core strengthening, and posture correction. Results showed marked improvement: participants scoring <50% decreased from 36% to 4%, while 80% achieved scores ≥70, confirming the effectiveness of practice-based community education in open space.